The effectiveness of the scamper strategy in innovative thinking for a teaching methods subject Physical Education and Sports Science (Journal of the College of Basic Education, 2022)
The first chapter included the introduction and the importance of research in finding a new strategy to know its effectiveness in innovative thinking for the subject of teaching methods of physical education and sports sciences. It is important to present a kind of modern strategies such as the Scamper strategy. College of Physical Education and Sports Sciences, third stage. Identifying the impact of Scamper's strategy on innovative thinking for teaching methods for students of the College of Physical Education and Sports Sciences for the third stage. The second chapter included the research methodology and its field procedures, and the researcher used the experimental method in the style of equal experimental samples. The research community was determined by the intentional method, and they are the third-stage students in the College of Physical Education and Sports Sciences, Wasit University, who numbered (100) students. (C-D) and their number is (40) students to represent Division (C) the control group and Division (D) the experimental group to represent each group (20) students, so that the research sample constitutes (50%) of the research community. For the purpose of the pilot experiment, (10) students were randomly selected from the research sample. The sample of the preparation included the entire research community and they are the students of the third stage. It reached (12) educational units, the time of the educational unit (90) minutes. The third chapter included presentation, analysis and discussion of the results, and included a detailed presentation of the results of all tests. The fourth chapter included the most important conclusions, which are that the Scamper strategy has a positive impact on the development of innovative thinking for the subject of teaching methods for third-year students in the College of Physical Education and Sports Sciences - Wasit University. The scamper strategy contributed to increasing the students' self-confidence by giving them the opportunity to generate and apply ideas. The researcher recommends the use of the scamper strategy by teachers in developing the innovative thinking of third-year students because of its role in raising their scientific level in teaching methods. Positively involving the students in the lesson and urging them to use their maximum potential and abilities in learning and developing their innovative thinking, as well as the need to use the Scamper strategy because it has effective countries in raising the level of knowledge among students